Skills recognition and validation - complexity and tensions - Cavaco, Carmen [Verfasser] (My University, 2010)
"This article seeks to identify and examine the reasons for the complexity and tensions underlying the skills recognition, accreditation and certification scheme (SRAC) that has been in place in Portugal since 2001. Empirical data were collected through semi-directive interviews with staff in three Centros Novas Oportunidades [CNOs] [New Opportunity Centres] (organisations delivering the SRAC process), and biographical interviews with adults who have completed the scheme. The complex nature of the assumptions associated with skills recognition and accreditation practices and the tensions raised by their underlying paradox are important factors. It is the particular features of the aspects that SRAC practices analyse and assess, i.e. prior experiential learning, that generate this complex nature. These practices are marked by a paradox that arises because these processes, initially based on a humanist approach, are currently linked to a very different ideology. This complexity and these tensions are reflected in the way skills recognition and accreditation schemes are organised and function, and are evident in the comments of staff in the CNOs studied, who play a key role in managing such complexities and tensions." (Autorenreferat, BIBB-Doku)
Keywords: L 2.1.3 Erfahrungslernen; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; I 2.2.1 Westeuropa; Erfahrungsorientiertes Lernen; Anerkennung; Zertifizierung; Erwachsenenbildung; Portugal